So to factor
factor out a x+z
(x+z)(x^2-xz+z^2)
the factors are
x+z and x^2-xz+z^2
Answer:
Simplify the expression.
28.5q−2
Step-by-step explanation:
i think this what you would like
Answer:
I need sum more detail to answer just email me and we can get this dun.
Step-by-step explanation:
If there are 6 friends and half as many food bars as friends, then each friend would get half a food bar. How that each of the 3 food bars are split in half, there is 6 pieces for the 6 friends! :)
Answer:
a1 = 6
a2 = 15
a3 = 24
a4 = 33
Step-by-step explanation:
Let k =1
a1 =-3 +9(1) = -3 +9 = 6
Let k = 2
a2 = -3 +9(2) =-3+18 = 15
Let k =3
a3 =-3 +9(3) = -3 +27 = 24
Let k = 4
a4 = -3 +9(4) =-3+36 = 33